Intercooperative Relationships: characteristics, challenges and possibilities for Interorganizational Cost Management - Rufato da Silva, Marivânia; Bernardes Voese, Simone (Revista de Negócios, 2021)
This study aims at discussing the characteristics of intercooperative relationships and the challenges and possibilities for Interorganizational Cost Management (IOCM) in these arrangements. For this, the theoretical essay method was used to review the national and international literature in the area ofÂ cooperatives. Thus, based on the literature and having the Contingency Theory (CT) as a theoretical lens, a contingency structure of the IOCM was proposed, consisting of eleven factors grouped into "factors exogenous to the cooperative", "factors specific to the cooperative" and "factors specific to the intercooperative relationshipâ€. The results of the analysis show that: (i) factors external to the cooperatives can make the adoption of the IOCM viable, such as pressure for financial competitiveness and multiple objectives; (ii) specific factors of cooperatives, such as small size trends and shortage of capital, are challenges to IOCM; and (iii) factors specific to intercooperative relationships, such as lack of trust and competition, can restrict the adoption of IOCM techniques and the very formation of intercooperative relationships. It is noteworthy that while CT conventionally works with the perspective of a single company, this essay highlights possibilities of its application in interorganizational relationships, considering relationship factors beyond those specific to the company. Furthermore, on the theme of IOCM, no studies applied to intercooperative relationships were identified. It is concluded that the research can bring new perspectives to researchers, especially on the topic of management in cooperative societies, with reflections both on the adoption of IOCM techniques, as well as on the constitution and performance of intercooperative relationships.Â Â